A halide electrolyte material, and a method of making and using the same

CN123018115APending Publication Date: 2026-10-30ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611501651.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]然而,现有卤化物固态电解质(如等)在产业化进程中面临多重挑战:一方面,其空气稳定性差,暴露在潮湿环境中易水解生成腐蚀性HCl气体,导致结构坍塌;另一方面,其较高的还原电位使其与金属锂或低电位负极(如石墨、硅)直接接触时易发生分解反应,限制了其在负极侧及电解质层的应用

Benefits of technology

[0020]本申请提供一种卤化物电解质材料及其制备方法和应用,通过非晶态钽基卤化物电解质与第一包覆层的协同设计,显著提升卤化物电解质材料电化学窗口、空气稳定性及与正、负极材料适配性。非晶态钽基卤化物电解质的无序结构降低了锂离子迁移势垒,同时避免晶界处的离子传输瓶颈;第一包覆层通过的引入及X元素的协同作用进一步拓宽了材料的电化学窗口。通过内核与包覆层的协同增效,本申请复合卤化物电解质兼具宽电化学稳定窗口及优异空气稳定性,适配全固态电池正极及固态电解质层使用,与正负极材料具备优良界面相容性,可显著改善全固态电池的循环稳定性与倍率充放电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018115A_ABST
    Figure CN123018115A_ABST
Patent Text Reader

Abstract

The application provides a halide electrolyte material and a preparation method and application thereof. The halide electrolyte material comprises an electrolyte base and a first coating layer existing on the surface of the electrolyte base. The electrolyte base comprises an amorphous tantalum-based halide electrolyte. The first coating layer comprises a rare earth lithium salt. The rare earth lithium salt comprises Li2aXbZ, wherein 0<=a<=0.3, 0<=b<=0.1, X comprises at least two halogen elements in F, Cl, Br and I, and Z comprises at least one element in O, S and Se. The halide electrolyte material has a wide electrochemical window, good air stability and adaptability to positive and negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery technology, specifically to a halide electrolyte material, its preparation method, and its application. Background Technology

[0002] Solid-state batteries, as the ultimate form of next-generation power batteries, are being widely used in new energy vehicles, energy storage systems, and consumer electronics. Their core advantage lies in completely eliminating traditional liquid electrolytes and separators, using solid electrolytes to achieve lithium-ion conduction, thus achieving breakthroughs in safety and performance in material systems, internal structures, and working mechanisms. In the field of new energy vehicles, the high energy density of solid-state batteries can significantly improve driving range, while their inherent safety effectively avoids the risk of thermal runaway, meeting the needs of use under extreme conditions. In energy storage systems, the long cycle life and wide temperature range adaptability of solid-state batteries can support large-scale power storage and distributed energy management. In the field of consumer electronics, their lightweight and flexible design characteristics are compatible with emerging products such as wearable devices and foldable screen phones.

[0003] However, existing halide solid electrolytes (such as Halogenated electrolytes (such as lithium metal and silicon) face multiple challenges in their industrialization process: on the one hand, their poor air stability makes them prone to hydrolysis in humid environments, generating corrosive HCl gas and causing structural collapse; on the other hand, their high reduction potential makes them susceptible to decomposition reactions when in direct contact with metallic lithium or low-potential anodes (such as graphite and silicon), limiting their application on the anode side and in the electrolyte layer. Furthermore, while traditional surface coating processes can improve stability, they often come at the cost of sacrificing ionic conductivity, leading to a disconnect between electrolyte performance and application requirements. Therefore, developing halide electrolyte materials that combine a wide electrochemical window, excellent air stability, and compatibility with both positive and negative electrode materials has become an urgent technical problem to be solved in this field. Summary of the Invention

[0004] This application provides a halide electrolyte material, its preparation method, and its application. The halide electrolyte material has a wide electrochemical window, excellent air stability, and compatibility with positive and negative electrode materials.

[0005] This application provides a halide electrolyte material, including an electrolyte matrix and a first coating layer present on the surface of the electrolyte matrix; the electrolyte matrix includes an amorphous tantalum-based halide electrolyte; the first coating layer includes a rare earth lithium salt, wherein the rare earth lithium salt includes... Where 0≤a≤0.3, 0≤b≤0.1, X includes at least two halogen elements from F, Cl, Br, and I, Z includes at least one element from O, S, and Se, Y is yttrium, and N is nitrogen.

[0006] According to one embodiment of this application, in the halide electrolyte material, based on 1 mol of the electrolyte matrix, the... The molar amount y satisfies 0.01≤y≤0.5; and / or, the amorphous tantalum-based halide electrolyte includes lithium tantalum oxyhalide.

[0007] According to one embodiment of this application, based on 1 mol of the electrolyte matrix, the... The molar quantity y satisfies 0.01 ≤ y ≤ 0.3;

[0008] And / or, the lithium tantalum oxyhalide includes Based on 1 mol TaCl5, the molar amount x of Li2O satisfies 0.4 ≤ x ≤ 2.5.

[0009] According to one embodiment of this application, the halide electrolyte material further includes a second coating layer located on the side of the first coating layer opposite to the electrolyte matrix; the second coating layer includes an inorganic metal compound, the inorganic metal compound including , 1≤c≤3, 1≤d≤5; M includes one or more of Sn, Zn, and Al, Q includes halogen elements and / or non-halogen elements, wherein the halogen elements include at least one of F, Cl, Br, and I, and the non-halogen elements include at least one of O, S, and Se; and / or, the oxidation potential of the halide electrolyte material is 3.58V~4.50V, and the reduction potential is 1.18V~1.90V.

[0010] According to one embodiment of this application, in the halide electrolyte material, based on 1 mol of the electrolyte matrix, the second coating layer contains... The molar amount z satisfies 0.01≤z≤0.2; and / or, the XRD spectrum of the halide electrolyte material has diffraction peaks at 2θ of 13.5°±0.5°, 25°±0.5°, 26.5°±0.5°, 28°±0.5°, 32°±0.5°, 33.5°±0.5°, 46°±0.5°, and 51.5°±0.5°.

[0011] According to one embodiment of this application, based on 1 mol of the electrolyte matrix, the second coating layer contains... The molar amount z satisfies 0.01≤z≤0.05.

[0012] This application also provides a method for preparing a halide electrolyte material, comprising the following steps: performing a first ball milling treatment on an electrolyte matrix and a rare earth lithium salt to form a first coating layer on the surface of the electrolyte matrix, thereby obtaining the halide electrolyte material; wherein the electrolyte matrix comprises an amorphous tantalum-based halide electrolyte, and the rare earth lithium salt comprises... Wherein, 0≤a≤0.3, 0≤b≤0.1, X includes at least two halogen elements selected from F, Cl, Br, and I, and Z includes at least one element selected from O, S, and Se.

[0013] According to one embodiment of this application, in the method for preparing the halide electrolyte material, the first ball milling treatment is performed at a rotation speed of 200 rpm to 300 rpm for a time of 3 to 10 h; and / or, the method for preparing the amorphous tantalum-based halide electrolyte includes: subjecting a mixture of a lithium source and a tantalum source to a second ball milling treatment under an inert atmosphere to obtain the amorphous tantalum-based halide electrolyte; wherein at least one of the lithium source and the tantalum source contains a halogen.

[0014] According to one embodiment of this application, in the method for preparing the halide electrolyte material, the second ball milling treatment is performed at a rotation speed of 600 rpm to 850 rpm for a time of 2 to 48 hours; and / or, the lithium source includes LiF, LiCl, LiBr, LiI, LiOH, etc. , One or more of the following; and / or, the tantalum source includes One or more of TaC.

[0015] According to one embodiment of this application, the preparation method of the halide electrolyte material further includes: obtaining a ball-milled product after the first ball milling treatment; mixing the ball-milled product with an inorganic metal compound and then subjecting it to rotary heating to form a second coating layer on the surface of the first coating layer away from the electrolyte matrix, thereby obtaining the halide electrolyte material.

[0016] According to one embodiment of this application, in the method for preparing the halide electrolyte material, the temperature of the rotary heating is 60℃~150℃ and the time is 1~5h; and / or, the rotation speed of the rotary heating is 5rpm~300rpm.

[0017] This application embodiment also provides a positive electrode sheet, including a positive current collector and a positive active material layer. The positive active material layer includes a positive active material, a conductive agent, and a solid electrolyte. The solid electrolyte includes the halide electrolyte material described above or a halide electrolyte material prepared by the preparation method described above.

[0018] This application also provides a solid electrolyte membrane, including the halide electrolyte material described above or the halide electrolyte material prepared by the above preparation method.

[0019] This application also provides a solid-state battery, including a positive electrode, a negative electrode, and a solid electrolyte membrane, wherein the solid electrolyte membrane is disposed between the positive electrode and the negative electrode, the positive electrode includes the aforementioned positive electrode, and the solid electrolyte membrane includes the aforementioned solid electrolyte membrane.

[0020] This application provides a halide electrolyte material, its preparation method, and its application, through the interaction of an amorphous tantalum-based halide electrolyte with... The synergistic design of the first coating layer significantly improves the electrochemical window, air stability, and compatibility with positive and negative electrode materials of the halide electrolyte material. The disordered structure of the amorphous tantalum-based halide electrolyte lowers the lithium-ion migration barrier while avoiding ion transport bottlenecks at grain boundaries; the first coating layer, through... The introduction of [a specific ingredient] and the synergistic effect of element X further broaden the electrochemical window of the material. Through the synergistic effect of the core and the coating layer, the composite halide electrolyte of this application has both a wide electrochemical stability window and excellent air stability, making it suitable for use in the positive electrode and solid electrolyte layer of all-solid-state batteries. It has excellent interfacial compatibility with positive and negative electrode materials and can significantly improve the cycle stability and rate charge / discharge performance of all-solid-state batteries. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the structure of the halide electrolyte material in one embodiment of this application;

[0022] Figure 2 This is a schematic diagram of the structure of the halide electrolyte material in another embodiment of this application;

[0023] Figure 3 The X-ray diffraction (XRD) patterns of the halide electrolyte materials in Examples 36, 26 and Comparative Example 2 of this application are shown.

[0024] Explanation of reference numerals in the attached figures:

[0025] 1-Electrolyte matrix, 2-First coating layer, 3-Second coating layer. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0027] This application provides a halide electrolyte material, such as Figure 1As shown, it includes an electrolyte substrate 1 and a first coating layer 2 present on the surface of the electrolyte substrate 1; the electrolyte substrate 1 includes an amorphous tantalum-based halide electrolyte; the first coating layer 2 includes a rare earth lithium salt, the rare earth lithium salt including Where 0 ≤ a ≤ 0.3, 0 ≤ b ≤ 0.1, X includes at least two halogen elements selected from F, Cl, Br, and I, and Z includes at least one element selected from O, S, and Se. Y is yttrium, and N is nitrogen.

[0028] This application uses an amorphous tantalum-based halide electrolyte as its core, and coats it with a first coating layer containing rare-earth lithium salt for synergistic composite modification, significantly improving the electrochemical window, air stability, and compatibility with positive and negative electrode materials of the halide electrolyte material. Specifically, the amorphous tantalum-based halide core possesses a disordered microstructure, which can effectively reduce the lithium-ion migration barrier, eliminate grain boundary blocking effects, and reduce grain boundary impedance; the first coating layer containing rare-earth lithium salt... The rare-earth lithium salt can form a continuous lithium-ion conduction pathway with X, giving the halide electrolyte material a high lithium migration rate. Simultaneously, this rare-earth lithium salt broadens the overall electrochemical stability window of the composite electrolyte, effectively suppressing interfacial side reactions between the electrode and the electrolyte. By introducing at least one element from O, S, Se, and N into the first coating layer, a multi-element heteroatom synergistic optimization of the lithium-ion pathway is formed, widening the electrochemical window, enhancing the bonding force between the first coating layer and the substrate, and further suppressing hydrolysis and interfacial reduction side reactions. Through the synergistic effect of the core and the coating layer, the composite halide electrolyte of this application possesses a wide electrochemical stability window, excellent air stability, and compatibility with both positive and negative electrode materials. It is suitable for use in the positive electrode and solid electrolyte layer of all-solid-state batteries, exhibiting excellent interfacial compatibility with both positive and negative electrode materials, and can significantly improve the cycle stability and rate charge / discharge performance of all-solid-state batteries.

[0029] In this embodiment, 1 mol of electrolyte matrix is ​​used as the reference. The molar amount y satisfies 0.01≤y≤0.5, preferably 0.01≤y≤0.3. On the one hand, this ensures the system contains a sufficient amount of disordered amorphous tantalum-based halide as a fast lithium-ion conduction framework, fully utilizing its advantages of low migration barrier and low grain boundary resistance to improve the ion conductivity of halide electrolyte materials. On the other hand, it facilitates... A dense and continuous first coating layer is formed on the surface of the electrolyte matrix, which further improves the ionic conductivity and interfacial stability of the halide electrolyte material.

[0030] For example, based on 1 mol of electrolyte matrix, the molar amount x of amorphous tantalum-based halide electrolyte can be 0.4, 0.8, 1.2, 1.6, 2.0, 2.5, or any combination of the above.

[0031] For example, using 1 mol of electrolyte matrix as a reference, The molar quantity y can be 0.01, 0.05, 0.1, 0.15, 0.2, 0.3, 0.4, 0.5, or any combination of the above.

[0032] In some embodiments, the amorphous tantalum-based halide electrolyte includes lithium tantalum oxyhalide. Oxygen helps optimize lithium transport channels, broaden the electrochemical window, strengthen the interfacial bonding between the electrolyte matrix and the coating layer, while also mitigating halide hydrolysis and improving the ionic conductivity and air stability of the halide electrolyte material.

[0033] In some embodiments, lithium tantalum oxyhalide includes , with 1 mol Based on, The molar amount x satisfies 0.4≤x≤2.5, preferably 0.5≤x≤1, which is beneficial to further improve the ionic conductivity and air stability of the halide electrolyte material.

[0034] In the embodiments of this application, such as Figure 2 As shown, the halide electrolyte material also includes a second coating layer 3 located on the side of the first coating layer 2 facing away from the electrolyte matrix 1. The second coating layer 3 includes an inorganic metal compound, which includes... 1≤c≤3 (e.g., 1, 2, 3), 1≤d≤5 (e.g., 1, 2, 3, 4, 5); M includes one or more of Sn, Zn, and Al; Q includes halogens and / or non-halogens, where halogens include at least one of F, Cl, Br, and I, and non-halogens include at least one of O, S, and Se. Second coating layer By physically preventing direct contact between humid air and the electrolyte, the hydrolysis reaction is inhibited. Furthermore, by chemically adsorbing and neutralizing the HCl gas produced during hydrolysis, the crystal structure stability of the halide electrolyte material is improved, further enhancing its air stability.

[0035] In some embodiments, the oxidation potential of the halide electrolyte material is 3.58V~4.50V, and the reduction potential is 1.18V~1.90V. This facilitates the formation of a wide electrochemical stability window suitable for high-voltage battery systems, improving battery energy density; effectively avoiding electrolyte reduction decomposition and metal precipitation, reducing interfacial side reactions, stabilizing interfacial impedance, and further improving the battery's rate charge / discharge performance and long-term cycle stability.

[0036] For example, the oxidation potential of the halide electrolyte material can be 3.58V, 3.8V, 3.9V, 4V, 4.1V, 4.2V, 4.3V, 4.4V, 4.5V, or any combination of the above.

[0037] For example, the reduction potential of the halide electrolyte material can be 1.18V, 1.3V, 1.4V, 1.5V, 1.6V, 1.7V, 1.8V, 1.9V, or any combination thereof.

[0038] In this embodiment, the electrochemical window of the halide electrolyte material is determined by linear scanning voltammetry to obtain the oxidation and reduction potentials of the halide electrolyte material: The halide electrolyte to be tested is placed in a battery mold with a diameter of 10 mm. Solid electrolyte powder is layered and first pressed into a double-layer electrolyte sheet under a pressure of 200 MPa; then... A lithium foil was attached to the side of the electrolyte layer opposite to the halide electrolyte layer under test. Stainless steel current collectors were placed above and below the double-layer electrolyte sheet, and the sheet was pressurized to form a shape under 50 MPa. Linear sweep voltammetry was then performed with a scan range of 1.0–6.0 V and a scan rate of 0.1 mV / s. Tangents were drawn to the oxidation and reduction peaks of the curves, and the intersections of the tangents with the horizontal axis corresponded to the oxidation and reduction potentials of the material.

[0039] In this embodiment, 1 mol of electrolyte matrix is ​​used as the reference. The molar amount z satisfies 0.01≤z≤0.2, preferably 0.01≤z≤0.05.

[0040] For example, using 1 mol of electrolyte matrix as a reference, The molar amount z can be 0.01, 0.03, 0.05, 0.07, 0.09, 0.11, 0.13, 0.15, 0.17, 0.19, 0.2, or any combination of the above.

[0041] In some implementations... Including inorganic metal compounds. Examples include: AlN ZnO, ZnS , SnO SnS One or more of them.

[0042] In some embodiments, the XRD patterns of the halide electrolyte material exhibit diffraction peaks at 2θ values ​​of 13.5°±0.5°, 25°±0.5°, 26.5°±0.5°, 28°±0.5°, 32°±0.5°, 33.5°±0.5°, 46°±0.5°, and 51.5°±0.5°. The diffraction peaks at 2θ = 13.5°±0.5° and 25°±0.5° correspond to the characteristic disordered structure of amorphous tantalum-based halide electrolytes; the diffraction peaks at 26.5°±0.5° and 51.5°±0.5° correspond to the crystalline characteristics of rare-earth lithium salts, verifying their uniform coating on the electrolyte matrix surface.

[0043] This application embodiment also provides a method for preparing the above-mentioned halide electrolyte material, comprising the following steps: performing a first ball milling treatment on an electrolyte matrix and a rare earth lithium salt to form a first coating layer on the surface of the electrolyte matrix, thereby obtaining the halide electrolyte material; the electrolyte matrix includes an amorphous tantalum-based halide electrolyte, and the rare earth lithium salt includes... Wherein, 0≤a≤0.3, 0≤b≤0.1, X includes at least two halogen elements selected from F, Cl, Br, and I, and Z includes at least one element selected from O, S, and Se.

[0044] In some embodiments, the first ball milling process is carried out at a rotation speed of 200 rpm to 300 rpm for 3 to 10 hours. This facilitates the refinement of electrolyte matrix particles and simultaneously drives... The coating spreads and bonds at the surface of the electrolyte matrix, forming a complete and continuous first coating layer.

[0045] In some embodiments, the preparation method of the amorphous tantalum-based halide electrolyte includes: subjecting a mixture comprising a lithium source and a tantalum source to a second ball milling process under an inert atmosphere to obtain the amorphous tantalum-based halide electrolyte; wherein at least one of the lithium source and the tantalum source contains a halogen. Preferably, the inert atmosphere includes nitrogen. An inert atmosphere is beneficial for isolating water vapor and inhibiting halide hydrolysis. The amorphous tantalum-based halide electrolyte is synthesized in one step via a mechanochemical reaction.

[0046] In some embodiments, the second ball milling process is carried out at a rotation speed of 600 rpm to 850 rpm for 2 to 48 hours. This facilitates the complete amorphous conversion of the mixture including lithium and tantalum sources, forming an amorphous tantalum-based halide electrolyte.

[0047] In some embodiments, the lithium source includes LiF, LiCl, LiBr, LiI, LiOH, , One or more of them.

[0048] In some implementations, the tantalum source includes One or more of TaC.

[0049] In this embodiment, the method further includes: obtaining a ball-milled product after a first ball milling process; mixing the ball-milled product with an inorganic metal compound and then subjecting it to rotary heating to form a second coating layer on the surface of the first coating layer away from the electrolyte matrix, thereby obtaining a halide electrolyte material. Specifically, during the rotary heating process, the rotary heating equipment can drive the material to tumble uniformly, causing the inorganic metal compound to be uniformly deposited on the surface of the first coating layer, forming a continuous physical barrier layer (i.e., the second coating layer); at the same time, under heating conditions, the active sites on the surface of the first coating layer can chemically adsorb the inorganic metal compound, strengthening the interfacial bonding strength between the second coating layer and the first coating layer.

[0050] In some embodiments, the rotary heating temperature is 60°C to 150°C, and the time is 1 to 5 hours.

[0051] In some implementations, the rotational heating speed is 5 to 300 rpm.

[0052] In some embodiments, the rotary heating equipment includes one or more of the following: a rotary tube furnace, a rotary evaporator, a heated magnetic stirrer, and a rotary kiln.

[0053] In some implementations, according to rare earth lithium salts Based on the stoichiometric ratio, the raw materials containing YX3, LiX, and a non-halogen anion lithium source were weighed, and the raw materials were sequentially subjected to sintering and powder refining treatments to obtain rare earth lithium salts. X includes at least one halogen element selected from F, Cl, Br, and I. Non-halogen anionic lithium sources include Li₂O, , One or more of them.

[0054] In some embodiments, the sintering process is carried out in a quartz crucible.

[0055] In some implementations, rare earth lithium salts The particle size D50 is 1μm~5μm.

[0056] In this embodiment, rare earth lithium salts The particle size D50 can be measured using conventional methods in the art for measuring lithium salt particle size D50, such as laser diffraction particle size analysis.

[0057] This application also provides a positive electrode sheet, including a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer includes a positive electrode active material, a conductive agent, and a solid electrolyte. The solid electrolyte includes the halide electrolyte material described above or a halide electrolyte material prepared by the above-described preparation method. The halide electrolyte material can form a good ion transport network in the positive electrode sheet, promoting the full utilization of the capacity of the positive electrode active material.

[0058] Generally, in the positive electrode active material layer, the mass percentage of the positive electrode active material can be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 93%, 95%, 97%, 99%, or any combination thereof. The mass fraction of the conductive agent can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15%, or any combination thereof. The positive electrode active material layer also includes a binder, and the mass fraction of the binder can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15%, or any combination thereof.

[0059] In some embodiments, the positive electrode active material includes, but is not limited to, one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium-rich manganese-based materials, and nickel-cobalt-manganese ternary materials.

[0060] In the embodiments of this application, the conductive agent in the positive electrode active material layer can be a conventional conductive material in the art. For example, the conductive agent in the positive electrode active material layer may include one or more of conductive carbon black, conductive graphite, carbon nanotubes (CNTs), carbon fibers, graphene, acetylene black, and Ketjen black.

[0061] In this embodiment, the binder in the positive electrode active material layer can be a conventional binder in the art. For example, the binder in the positive electrode active material layer may include polytetrafluoroethylene (PTFE).

[0062] The embodiments of this application may employ conventional positive current collectors in the art, such as aluminum foil or carbon-coated aluminum foil.

[0063] In this embodiment, the positive electrode sheet can be prepared by conventional methods in the art, such as by dry preparation. Specifically, the positive electrode active material, conductive agent, and the above-mentioned halide electrolyte material used to form the positive electrode active material layer can be mixed to obtain a positive electrode dry powder. The positive electrode dry powder is laid on one side of the positive electrode current collector and rolled to make the positive electrode dry powder adhere tightly to the surface of the positive electrode current collector and form a positive electrode active material layer, thus obtaining the positive electrode sheet.

[0064] This application also provides a solid electrolyte membrane, comprising the halide electrolyte material described above or the halide electrolyte material prepared by the above-described preparation method. This solid electrolyte membrane has advantages corresponding to the halide electrolyte materials described above, which will not be elaborated upon here.

[0065] This application also provides a solid-state battery, including a positive electrode, a negative electrode, and a solid electrolyte membrane. The solid electrolyte membrane is disposed between the positive electrode and the negative electrode. The positive electrode includes the aforementioned positive electrode, and the solid electrolyte membrane includes the aforementioned solid electrolyte membrane.

[0066] The present application will be further described below through specific embodiments.

[0067] Example 1

[0068] The preparation method of halide electrolyte materials includes the following steps:

[0069] 1) By and Weigh the raw materials at a molar ratio of 0.5:1. and A total of 20g was placed in a ball mill jar with a ball-to-material ratio of 20:1. Under a nitrogen atmosphere, a second ball milling treatment was performed at 750 rpm for 15 hours to obtain 0.5g of amorphous tantalum-based halide electrolyte. .

[0070] 2) Using 1 mol 0.5 Based on this, in an amorphous tantalum-based halide electrolyte of 0.5... 0.03 mol of rare earth lithium salt with a particle size D50 of 1 μm was added. The first ball milling process was performed at 200 rpm for 2 hours to form a layer containing [a specific substance] on the surface of the amorphous tantalum-based halide electrolyte. The first coating layer yields a 0.5 mmol / L halide electrolyte material. .

[0071] Examples 2-10

[0072] The difference from Example 1 is that the amorphous tantalum-based halide electrolyte is 0.5... With rare earth lithium salts The molar amounts x and y are different, and both x and y are based on 1 mol of electrolyte matrix. For details, please refer to Table 1. Except for the differences shown in Table 1, the other steps and conditions are basically the same as in Example 1.

[0073] Examples 15-26

[0074] The difference from Example 1 is that in the preparation method of the halide electrolyte material, the first coating layer (i.e., the modification layer) is a rare earth lithium salt. The content and proportion of each element in the sample are different, as shown in Table 1. Except for the differences shown in Table 1, the other steps and conditions are basically the same as in Example 1.

[0075] Example 27

[0076] The preparation method of halide electrolyte materials includes the following steps:

[0077] 1) By and 20g of raw material was weighed out at a molar ratio of 0.75:1 and placed in a ball mill jar with a ball-to-material ratio of 20:1. Under a nitrogen atmosphere, a second ball milling treatment was performed at 750 rpm for 15 hours to obtain 0.75g of amorphous tantalum-based halide electrolyte. .

[0078] 2) Using 1 mol 0.75 Based on the baseline, in an amorphous tantalum-based halide electrolyte of 0.75... Add 0.21 mol of a particle size D50 of 1 rare earth lithium salts The first ball milling process was performed at 200 rpm for 2 hours to form a layer containing [a specific substance] on the surface of the amorphous tantalum-based halide electrolyte. The first coating layer yields a halide electrolyte. .

[0079] 3) Disperse tetraethyltin in a halide electrolyte The surface of the halide electrolyte is subjected to heat treatment at 120°C for 2 hours, with 95% nitrogen and 5% ozone (volume percentage) introduced into the rotary tube furnace at 5 rpm, to form a layer containing... The second coating layer yields the halide electrolyte material. .

[0080] Examples 28-31

[0081] The difference from Example 27 is that, in the preparation method of the halide electrolyte material, the second coating layer is an inorganic metal compound. The molar amount z varies, but z is based on 1 mol of electrolyte matrix. For details, please refer to Table 1. Except for the differences shown in Table 1, the other steps and conditions are basically the same as in Example 27.

[0082] Example 32

[0083] The preparation method of halide electrolyte materials includes the following steps:

[0084] 1) By and Weigh the raw materials at a molar ratio of 0.75:1. and A total of 20g was placed in a ball mill jar with a ball-to-material ratio of 20:1 and subjected to a second ball milling treatment at 750 rpm for 15 hours to obtain 0.75g of amorphous tantalum-based halide electrolyte. .

[0085] 2) Using 1 mol 0.75 Based on the baseline, in an amorphous tantalum-based halide electrolyte of 0.75... 0.21 mol of rare earth lithium salt with a particle size D50 of 1 μm was added. The first ball milling process was performed at 200 rpm for 2 hours to form a layer containing [a specific substance] on the surface of the amorphous tantalum-based halide electrolyte. The first coating layer yields 0.75% halide electrolyte. .

[0086] 3) Tetraethyltin, aluminum trichloride, and titanium fluoride were dispersed in a halide electrolyte solution of 0.75 mL. The surface of the halide electrolyte is subjected to heat treatment at 120°C for 2 hours in a rotary tube furnace, with 95% nitrogen and 5% ozone introduced at 5 rpm, to form a layer containing... and The second coating layer yields a 0.75 ppm halide electrolyte material. 0.21 0.02 .

[0087] Examples 33-35

[0088] The difference from Example 32 is that, in the preparation method of the halide electrolyte material, the second coating layer is an inorganic metal compound. The molar amount z varies, but z is based on 1 mol of electrolyte matrix. For details, please refer to Table 1. Except for the differences shown in Table 1, the other steps and conditions are basically the same as in Example 32.

[0089] Example 36

[0090] The preparation method of halide electrolyte materials includes the following steps:

[0091] 1) By and Weigh the raw materials at a molar ratio of 0.75:1. and A total of 20g was placed in a ball mill jar with a ball-to-material ratio of 20:1 and subjected to a second ball milling treatment at 750 rpm for 15 hours to obtain 0.75g of amorphous tantalum-based halide electrolyte. .

[0092] 2) Using 1 mol 0.75 Based on the baseline, in an amorphous tantalum-based halide electrolyte of 0.75... 0.21 mol of rare earth lithium salt with a particle size D50 of 1 μm was added. The first ball milling process was performed at 200 rpm for 2 hours to form a layer containing [a specific substance] on the surface of the amorphous tantalum-based halide electrolyte. The first coating layer yields 0.75% halide electrolyte. .

[0093] 3) Disperse tetraethyltin, aluminum trichloride, titanium fluoride, and zinc chloride in 0.75 L of halide electrolyte. The surface of the material was heat-treated in a rotary tube furnace with 95% nitrogen and 7% ozone at 120°C for 2 hours at 5 rpm to obtain 0.75 mmol of halide electrolyte material. .

[0094] Examples 37-38

[0095] The difference from Example 36 is that the molar amount z of the second coating layer inorganic metal compound ZnO in the preparation method of the halide electrolyte material is different. z is based on 1 mol of electrolyte matrix. For details, please refer to Table 1. Except for the differences shown in Table 1, the other steps and conditions are basically the same as those in Example 36.

[0096] Comparative Example 1

[0097] The difference between this comparative example and Example 1 is that only 0.5g of amorphous tantalum-based halide electrolyte was prepared. Furthermore, it does not utilize amorphous tantalum-based halide electrolytes (0.5 ppm). With rare earth lithium salt 0.03 The composite processing specifically includes the following steps:

[0098] according to and Weigh the raw materials at a molar ratio of 0.5:1. and A total of 20g was placed in a ball mill jar with a ball-to-material ratio of 20:1 and subjected to a second ball milling treatment at 750rpm for 15h to obtain 0.5g of amorphous tantalum-based halide electrolyte. .

[0099] Comparative Example 2

[0100] The difference between this comparative example and Example 1 is that the method used in Example 1 is changed. and Amorphous tantalum-based halide electrolyte 0.5 was prepared with a molar ratio of 0.5:1. Replace with and Amorphous tantalum-based halide electrolyte 0.75 was prepared with a molar ratio of 0.75:1. And without using amorphous tantalum-based halide electrolyte 0.75 With rare earth lithium salt 0.03 The composite processing specifically includes the following steps:

[0101] according to and Weigh the raw materials at a molar ratio of 0.75:1. and A total of 20g was placed in a ball mill jar with a ball-to-material ratio of 20:1 and subjected to a second ball milling treatment at 750 rpm for 15 hours to obtain 0.75g of amorphous tantalum-based halide electrolyte. .

[0102] The chemical formulas of the halide electrolyte materials in each embodiment and comparative example are summarized in Table 1. Except for the differences shown in Table 1, the other conditions are essentially the same. For example, the chemical formula of the halide electrolyte material in Example 1 is 0.5. That is, based on 1 mol of electrolyte matrix. The molar amount is 0.03.

[0103] Table 1

[0104]

[0105]

[0106] X-ray diffraction (XRD) tests were performed on the halide electrolyte materials in the above embodiments and comparative examples. XRD is a common method for analyzing the composition and crystal structure of solid powder materials. High-energy X-rays produce specific signals when passing through a periodic material lattice. Materials with different crystal structures produce different interference signals; therefore, XRD can qualitatively and quantitatively analyze the crystal structure information of materials. The XRD diffraction mode used in this experiment... The tube voltage and tube current are 40 kV and 40 mA, respectively. To avoid exposing the electrolyte to air, the XRD test range is 10°-80°, the scan rate is 5° / min, and the step size is 0.02°. Figure 3 The X-ray diffraction (XRD) patterns of the halide electrolyte materials in Examples 36, 26, and Comparative Example 2 are shown below. Figure 3As shown, compared with Comparative Example 2, the XRD pattern of Example 26 has diffraction peaks at approximately 13.5°±0.5°, 28°±0.5°, 32°±0.5°, and 46°±0.5°; while Example 36 has diffraction peaks at approximately 13.5°±0.5°, 26.5°±0.5°, 28°±0.5°, 32°±0.5°, 33.5°±0.5°, 46°±0.5°, and 51.5°±0.5°.

[0107] Experimental Examples 1-38 and Comparative Examples 1-2:

[0108] The halide electrolyte materials obtained in the above embodiments and comparative examples were exposed for 4 hours and then added to the composite positive electrode to form a positive electrode layer. The corresponding electrolyte was used as the electrolyte layer, and lithium metal was used as the negative electrode to assemble an all-solid-state battery. Specifically:

[0109] 1. Preparation of the positive electrode:

[0110] ternary cathode material The halide electrolyte exposed for 4 hours and the binder (PTFE) are mixed at a mass ratio of 70:30:0.5 to obtain the positive electrode dry powder. The positive electrode dry powder is laid on the surface of the positive electrode current collector of the stainless steel sheet and rolled to make the positive electrode dry powder adhere tightly to the surface of the positive electrode current collector and form a positive electrode active material layer. The positive electrode active material layer and the stainless steel are combined to form a positive electrode sheet.

[0111] 2. Lithium metal is used as the negative electrode.

[0112] 3. Preparation of exposed halide solid electrolyte membranes:

[0113] After the halide electrolyte exposed for 4 hours is thoroughly mixed with the binder (PTFE) at a mass ratio of 100:0.5, the mixed material is rolled into shape to prepare a halide solid electrolyte membrane.

[0114] 4. All-solid-state battery assembly:

[0115] The above-mentioned positive electrode, halide solid electrolyte membrane, and lithium metal negative electrode are stacked and assembled in sequence to complete the preparation of the all-solid-state battery, and subsequent electrochemical performance testing is carried out.

[0116] The above-mentioned halide electrolytes were tested as follows:

[0117] 1) Ionic conductivity and air stability tests of halide electrolytes: 150 mg of powder was weighed and placed in a battery mold (inner diameter 10 mm), a pressure of 200 MPa was applied, and the AC impedance was tested using an electrochemical workstation. An external voltage of 10 mV was applied within a frequency range of 1 Hz to 1 MHz. The initial ionic conductivity of the halide electrolyte was calculated. After exposing the halide electrolyte to a low-humidity room with a dew point of -50 °C for 4 h, the ionic conductivity after exposure was measured under the same sample preparation and impedance testing conditions. The ionic conductivity retention rate = (ionic conductivity after 4 h / initial ionic conductivity) × 100%. The results are shown in Table 2.

[0118] 2) Oxidation and reduction potential tests of halide electrolytes: In a battery mold with a diameter of 10 mm, the above-mentioned halide electrolytes, Solid electrolyte powder is layered and first pressed into a double-layer electrolyte sheet under a pressure of 200 MPa; then... A lithium foil was stacked on the side of the electrolyte layer opposite to the halide electrolyte layer under test. Stainless steel current collectors were placed on the top and bottom of the double electrolyte layer, and the mixture was pressurized to form a double electrolyte layer at 50 MPa. Linear sweep voltammetry was then performed with a scan range of 1.0–6.0 V and a scan rate of 0.1 mV / s. The oxidation and reduction potentials of the material were determined by plotting tangents to the oxidation and reduction peaks of the test curves and intersecting them with the abscissa. The results are shown in Table 2.

[0119] Table 2

[0120]

[0121]

[0122] Analysis of Table 2 shows that Examples 1-10 optimized the halide electrolyte x y The proportion of γ in the electrolyte gradually decreases with increasing γ content, with the halide electrolyte being 0.5%. 0.21 The highest ionic conductivity was observed after 4 hours of exposure; Examples 11-14 optimized the proportion of x, with Example 11 exhibiting the highest ionic conductivity; Examples 15-26 adjusted the rare earth lithium salt. The content and proportion of elements in the electrolyte were optimized. In Example 26, the oxidation potential was higher than 4.3V, the reduction potential was 1.2V, and the ionic conductivity was >7mS / cm. Examples 27-38 optimized the content and proportion of the surface coating layer. With the introduction of the surface coating layer, the air stability of the electrolyte material was significantly improved. Example 36 had the best performance. After exposure at a dew point of -50℃ for 4 hours, the ionic conductivity retention rate was >85%, and the ionic conductivity was still higher than 6mS / cm.

[0123] The following tests were performed on the aforementioned all-solid-state battery:

[0124] 1) Initial discharge specific capacity: The solid-state battery was tested at 25℃ with a constant current charge and discharge cycle of 0.1C for 1 cycle, with a voltage range of 2.7-4.3V. The results are shown in Table 3.

[0125] 2) Long-cycle test: The solid-state battery was subjected to 200 cycles of constant current charge and discharge at 0.5C at 25℃, with a voltage range of 2.7-4.3V. The results are shown in Table 3.

[0126] 3) Rate testing: 5 cycles each at 0.1C, 0.5C, 1C and 2C. 2C / 0.1C capacity retention rate = (2C discharge specific capacity / 0.1C discharge specific capacity) × 100%. The results are shown in Table 3.

[0127] Table 3

[0128]

[0129] Solid electrolyte layers were prepared using the halide electrolyte materials obtained in Examples 1-14 and Comparative Examples 1-2, and all-solid-state batteries were assembled for charge-discharge testing. The test results showed that the halide electrolytes in Examples 1-14 and Comparative Examples 1-2 had poor compatibility with the lithium metal anode interface, easily forming a high-resistivity passivation layer, significantly increasing battery polarization, and failing to complete stable charge-discharge cycle tests. Table 3 shows that Examples 15-26 optimized rare-earth lithium salts... When the electrolyte material with the correct proportions and content is applied to the electrolyte layer and composite cathode material, the battery can cycle normally. Among them, Example 26 shows better cycle and rate performance. In Examples 27-38, the electrolyte material with the optimized surface coating layer in Example 36 has a capacity of more than 160 mAh / g after 200 cycles and shows the best rate performance.

[0130] The embodiments of this application have been described above. However, this application is not limited to the embodiments described above. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A halide electrolyte material, characterized in that, Includes an electrolyte matrix and a first coating layer present on the surface of the electrolyte matrix; The electrolyte matrix includes an amorphous tantalum-based halide electrolyte; The first coating layer comprises a rare earth lithium salt, wherein the rare earth lithium salt comprises Wherein, 0≤a≤0.3, 0≤b≤0.1, X includes at least two halogen elements from F, Cl, Br, and I, Z includes at least one element from O, S, and Se, Y is yttrium, and N is nitrogen.

2. The halide electrolyte material according to claim 1, characterized in that, Based on 1 mol of the electrolyte matrix, the The molar quantity y satisfies 0.01 ≤ y ≤ 0.5; And / or, the amorphous tantalum-based halide electrolyte includes lithium tantalum oxyhalide.

3. The halide electrolyte material according to claim 2, characterized in that, Based on 1 mol of the electrolyte matrix, the The molar quantity y satisfies 0.01 ≤ y ≤ 0.3; And / or, the lithium tantalum oxyhalide includes Based on 1 mol TaCl5, The molar quantity x satisfies 0.4≤x≤2.

5.

4. The halide electrolyte material according to claim 1 or 2, characterized in that, The halide electrolyte material further includes a second coating layer located on the side of the first coating layer opposite to the electrolyte matrix; The second coating layer comprises an inorganic metal compound, the inorganic metal compound comprising... , 1≤c≤3, 1≤d≤5; M includes one or more of Sn, Zn, and Al, Q includes halogen elements and / or non-halogen elements, wherein the halogen elements include at least one of F, Cl, Br, and I, and the non-halogen elements include at least one of O, S, and Se; And / or, the oxidation potential of the halide electrolyte material is 3.58V~4.50V, and the reduction potential is 1.18V~1.90V.

5. The halide electrolyte material according to claim 4, characterized in that, Based on 1 mol of the electrolyte matrix, in the second coating layer The molar amount z satisfies 0.01 ≤ z ≤ 0.2; And / or, the XRD pattern of the halide electrolyte material has diffraction peaks at 2θ of 13.5°±0.5°, 25°±0.5°, 26.5°±0.5°, 28°±0.5°, 32°±0.5°, 33.5°±0.5°, 46°±0.5°, and 51.5°±0.5°.

6. The halide electrolyte material according to claim 5, characterized in that, Based on 1 mol of the electrolyte matrix, in the second coating layer The molar amount z satisfies 0.01≤z≤0.

05.

7. A method for preparing a halide electrolyte material according to any one of claims 1-6, characterized in that, Includes the following steps: The electrolyte matrix and rare earth lithium salt are subjected to a first ball milling process to form a first coating layer on the surface of the electrolyte matrix, thereby obtaining the halide electrolyte material. The electrolyte matrix includes an amorphous tantalum-based halide electrolyte, and the rare earth lithium salt includes... Where 0≤a≤0.3, 0≤b≤0.1, X includes at least two halogen elements selected from F, Cl, Br, and I, and Z includes at least one element selected from O, S, and Se.

8. The method for preparing the halide electrolyte material according to claim 7, characterized in that, The first ball milling process is performed at a rotation speed of 200 rpm to 300 rpm for a duration of 3 to 10 hours. And / or, the method for preparing the amorphous tantalum-based halide electrolyte includes: subjecting a mixture of a lithium source and a tantalum source to a second ball milling process under an inert atmosphere to obtain the amorphous tantalum-based halide electrolyte; wherein at least one of the lithium source and the tantalum source contains a halogen.

9. The method for preparing the halide electrolyte material according to claim 8, characterized in that, The second ball milling process involves a rotation speed of 600 rpm to 850 rpm and a time of 2 to 48 hours. And / or, the lithium source includes LiF, LiCl, LiBr, LiI, LiOH, , One or more of the following; And / or, the tantalum source includes One or more of TaC.

10. The method for preparing the halide electrolyte material according to claim 7 or 8, characterized in that, Also includes: After the first ball milling process, the ball-milled product is obtained; The ball-milled product is mixed with an inorganic metal compound and then subjected to rotary heating to form a second coating layer on the surface of the first coating layer away from the electrolyte matrix, thereby obtaining the halide electrolyte material.

11. The method for preparing the halide electrolyte material according to claim 10, characterized in that, The rotary heating temperature is 60℃~150℃, and the time is 1~5h; And / or, the rotational heating speed is 5~300 rpm.

12. A positive electrode plate, characterized in that, It includes a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer includes a positive electrode active material, a conductive agent, and a solid electrolyte. The solid electrolyte includes the halide electrolyte material according to any one of claims 1-6 or the halide electrolyte material prepared by the preparation method according to any one of claims 7-11.

13. A solid electrolyte membrane, characterized in that, Includes the halide electrolyte material according to any one of claims 1-6 or the halide electrolyte material prepared by the preparation method according to any one of claims 7-11.

14. A solid-state battery, characterized in that, It includes a positive electrode, a negative electrode, and a solid electrolyte membrane, wherein the solid electrolyte membrane is disposed between the positive electrode and the negative electrode, the positive electrode includes the positive electrode as described in claim 12, and the solid electrolyte membrane includes the solid electrolyte membrane as described in claim 13.